IBN RUSYD MEETS RELIGION, PHILOSOPHY AND SCIENCE - adam gio amaliano (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Ibn Rusyd is one of the philosophers who sought to combine religion and philosophy based on Islamic teachings, such as his belief that philosophy is not incompatible with Islam. Even Muslims are required to study it or are encouraged to do so. This research seeks to learn about Ibn Rusyd's efforts in bringing religion, philosophy, and science together and the relevance of Ibn Rusyd's thinking in bringing religion, philosophy, and science together in modern life. The writer uses content analysis, a research method that employs procedures to draw valid conclusions from books and documents. An analysis of Ibn Rusyd's thoughts on harmonizing religion, philosophy, and science, by making a justification classification based on the capacity of Muslim religious understanding will substantially prove a point. Because basically, one's understanding of religion at a certain level will not be separated from the function of reason as a promoter of rational thought. Without reason, one will not be able to accept the truth of religion, even if it is at a low